Birth prevalence and survival of exomphalos in england and wales: 2005 to 2011. Issue 9 (1st September 2014) - Springett, Anna; Draper, Elizabeth S.; Rankin, Judith; Rounding, Catherine; Tucker, David; Stoianova, Sylvia; Wellesley, Diana; Morris, Joan K.
<x xml:space="preserve">Abstract</x> Background Exomphalos occurs in 2.2 per 10, 000 births with 76% of these babies surviving to discharge. The aim of this study was to determine the birth prevalence and survival of babies with this anomaly in England and Wales. Methods Six BINOCAR regional congenital anomaly registers in England and Wales (covering 36% of births) between 2005 and 2011 provided cases for this study. Cases included live births, stillbirths (24+ weeks' gestation), late miscarriages (20–23 weeks' gestation), and terminations of pregnancy with fetal anomaly. Results The overall birth prevalence was 3.8 (95% confidence interval [CI]: 3.6–4.0) per 10, 000 births; 1.4 (1.2–1.6) for isolated cases, 1.2 (1.1–1.4) for cases with multiple anomalies, and 1.2 (1.1–1.4) for cases with chromosomal anomalies. The live birth prevalence was 0.8 (0.7–0.9), 0.5 (0.4–0.6), and 0.1 (0.0–0.1) per 10, 000 live births, respectively. Edwards syndrome, congenital heart defects, and nervous system anomalies were the most common anomalies associated with exomphalos. A prenatal diagnosis was made in 83% of isolated, 95% of multiple, and 99% of chromosomal cases. Fifty‐five percent of isolated and multiple cases were live born, whereas 85% of cases with chromosomal anomalies resulted in a termination of pregnancy with fetal anomaly. The 1‐year survival of live born babies with an isolated exomphalos was 92% compared with 81% in cases with multiple anomalies and 27% in cases with chromosomal anomalies (p < 0.001). Conclusion We report a higher birth prevalence than has previously been reported. The proportion of infants surviving with exomphalos remained unchanged over the time period. Birth Defects Research (Part A) 100:721–725, 2014. © 2014 Wiley Periodicals, Inc.